Isla and the happily ever after - Perkins, Stephanie (Dutton Books, an imprint of Penguin Group (USA) LLC, 2014)
Isla has had a crush on classmate Josh since their freshman year at the School of America in Paris, but after a chance encounter over the summer in Manhattan they return to France for their senior year where they are forced to confront challenges every young couple in love must face.